Formulation of the Problem for Calculating the Stress State of a Pillar for a Longwall Recovery Room - Gogolin Vyacheslav (EDP Sciences, 2021)
Two statements of the problem of calculating the stress state of pillars for a longwall recovery room are proposed. In the first statement, this pillar is located in the coal seam and is not affected by the adjacent extracted panel. The second statement takes into account the geomechanical effect of the adjacent extracted panel. The calculation area consists of the following blocks: the coal seam, the goaf, and the inter-panel pillar. All blocks are affected by their own weight. The problems are solved using the finite element method with pre-determined limiting conditions of the stress state within the solid strata.